Desentralisasi atau Separasi? Suatu Tinjauan dari Sulawesi Selatan - Elizabeth Morrell (Antropologi Indonesia, 2002)
Perceived opportunities for increased local power and control of resources in the early euphoria of post-Soeharto decentralization saw no less than four new province proposals within the present boundaries of South Sulawesi. Two of those developed into formal submissions which, at the time of writing, are being considered by the national government. These are for new provinces of West Sulawesi and Greater Luwu, which would encompass approximately fifty-five per cent of South Sulawesi's present land mass. This article discusses those movements and the rationale behind their emergence. Residents in each region express dissatisfaction at long-term neglect by the South Sulawesi government. In particular, kabupatens calling for the establishment of West Sulawesi have been ignored in the development process. Following calls for the new province, the South Sulawesi leadership has promised increased recognition of the western regions. West Sulawesi and Luwu Raya are viewed as possessing high potential for resource development, particularly in plantation agriculture, fisheries, and mineral exploration. Ethnic identity has also been a factor in the new province demands. In some cases, preexisting ethnic tensions have been exacerbated by debates centered upon proposed province boundaries. Calls for change should be seen as a sign of dissatisfaction with the South Sulawesi leadership rather than with national governance, as new structures would by-pass present provincial authority, strengthening ties with the centre by allowing direct interaction between the respective regions and Jakarta.